2016
DOI: 10.1055/s-0042-107247
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training and Ovariectomy: Antagonic Effects in Mitochondrial Biogenesis Markers in Rat Skeletal Muscle

Abstract: Estrogen reduction is associated with a decline in skeletal muscle mitochondrial biogenesis. Molecular events associated with improvements in markers of mitochondrial biogenesis after resistance training and estradiol replacement are unknown. This study aimed to investigate the effects of ovariectomy, resistance training, and estradiol replacement on markers of mitochondrial biogenesis and protein expression related to oxidative capacity in the rat gastrocnemius pool. Estradiol replacement was performed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 44 publications
6
17
0
2
Order By: Relevance
“…This result corroborates with the findings of Barbosa, Shiguemoto, et al which seems to be the first study to present some changes in mitochondrial function in an experimental model of menopause [37]. Our results strengthen the evidence that reduction of estrogen levels is a problem of female physiology that requires further investigation.…”
Section: Ovariectomysupporting
confidence: 93%
See 1 more Smart Citation
“…This result corroborates with the findings of Barbosa, Shiguemoto, et al which seems to be the first study to present some changes in mitochondrial function in an experimental model of menopause [37]. Our results strengthen the evidence that reduction of estrogen levels is a problem of female physiology that requires further investigation.…”
Section: Ovariectomysupporting
confidence: 93%
“…However, RT yielded significantly higher the expression of PGC1-α as well as UCP1 in Ovx-RT. Our results corroborate with the findings of Barbosa, Shiguemoto, et al that also reported lower PGC1-α in Ovx rats and their study showed that the reduction of PGC1-α expression are accompanied by significant reductions in genes and proteins as TFAM and NRF1, which favor mitochondrial biogenesis and also improve the thermogenic machinery [37,[48][49][50]. These data represent an important contribution to understand the relation of exercise, higher mitochondrial biogenesis and thermogenic process as important strategy to prevent the effects of ovariectomy and development of some obesity-related dis-eases.…”
Section: Resistance Trainingsupporting
confidence: 93%
“…Notably, however, tissue analyses also demonstrated higher ERα mRNA expression in skeletal muscle from WT(ArKO) mice, suggesting the possibility that selective loss of aromatase activity in immune cells yielded a compensatory increase in total estradiol signaling within skeletal muscle. A compensatory increase in estradiol signaling is further supported by the fact that skeletal muscle from WT(ArKO) mice showed enhanced expression of genes that are specifically upregulated by 17β-estradiol, including those involved in mitochondrial biogenesis [30]. Further, systemic administration of 17β-estradiol to orchiectomized mice enhanced skeletal muscle glucose uptake due to upregulation of GLUT4 expression [31], another gene that exhibited increased expression in the WT(ArKO) mice relative to WT(WT) controls.…”
Section: Discussionmentioning
confidence: 93%
“…Assim, classificaram essa alteração como um quadro típico de sarcopenia e perda da força e tônus muscular, resultante do déficit hormonal nos grupos ooforectomizados. Barbosa et al (BARBOSA et al, 2016), ao utilizarem o modelo de ooforectomia e avaliarem o músculo plantar, relataram que esse apresenta quantidades equivalentes de fibras do tipo I e do tipo IIA, sendo chamado de músculo misto. De acordo com os pesquisadores, com apenas 12 dias de privação hormonal houve alterações morfológicas e morfométricas nas fibras musculares.…”
Section: Discussionunclassified